Co-operative additive effects between HLA alleles in control of HIV-1 - Matthews, Philippa C.; Listgarten, Jennifer; Carlson, Jonathan M.; Payne, Rebecca; Huang, Kuan-Hsiang Gary; Frater, John; Goedhals, Dominique; Steyn, Dewald; Vuuren, Cloete van; Paioni, Paolo; Jooste, Pieter; Ogwu, Anthony; et al. (PLoS ONE, 2012)
Background HLA class I genotype is a major determinant of the outcome of HIV infection, and the impact of certain alleles on HIV disease outcome is well studied. Recent studies have demonstrated that certain HLA class I alleles that are in linkage disequilibrium, such as HLA-A*74 and HLA-B*57, appear to function co-operatively to result in greater immune control of HIV than mediated by either single allele alone. We here investigate the extent to which HLA alleles - irrespective of linkage disequilibrium - function co-operatively. Methodology/Principal Findings We here refined a computational approach to the analysis of >2000 subjects infected with C-clade HIV first to discern the individual effect of each allele on disease control, and second to identify pairs of alleles that mediate ‘co-operative additive’ effects, either to improve disease suppression or to contribute to immunological failure. We identified six pairs of HLA class I alleles that have a co-operative additive effect in mediating HIV disease control and four hazardous pairs of alleles that, occurring together, are predictive of worse disease outcomes (q